E3 Ubiquitin Ligases in Breast Cancer Metastasis: A Systematic Review of Pathogenic Functions and Clinical Implications - Wang, Yingshuang; Dai, Jiawen; Zeng, Youqin; Guo, Jinlin; Lan, Jie (Frontiers in Oncology, 2021)
Female breast cancer has become the most commonly occurring cancer worldwide. Although it has a good prognosis under early diagnosis and appropriate treatment, breast cancer metastasis drastically causes of mortality. The process of metastasis, which includes cell epithelial-mesenchymal transition (EMT), invasion, migration and colonization, is a multistep cascade of molecular events directed by gene mutations and altered protein expressions. Ubiquitin modification of proteins plays a common role in most of the biological processes. E3 ubiquitin ligase, the key regulator of protein ubiquitination, determines the fate of ubiquitinated proteins. E3 ubiquitin ligases target a broad spectrum of substrates. Aberrant functions of many E3 ubiquitin ligases can affect the biological behavior of cancer cells, including breast cancer metastasis. In this review, we provide an overview of these ligases, summarize the metastatic processes in which E3s are involved, and comprehensively describe the roles of E3 ubiquitin ligases. Furthermore, we classified E3 ubiquitin ligases based on their structure and analyzed with survival of breast cancer patients. Finally, we consider how our knowledge can be used for E3s’ potency in therapeutic intervention or prognostic assessment of metastatic breast cancer.